Effects of the Antidepressant Fluoxetine on the Somatostatin Interneurons in the Basolateral Amygdala. (21st August 2018) - Carceller, Hector; Perez-Rando, Marta; Castren, Eero; Nacher, Juan; Guirado, Ramon
Highlights: Fluoxetine treatment induces alterations in inhibitory circuits of the amygdala. These alterations include increased density of neuropil structures expressing PSA-NCAM. Somatostatin interneurons show reduced structural features after Fluoxetine treatment. Abstract: Although the precise mechanism of action of antidepressant drugs remains elusive, the neuroplastic hypothesis has gained acceptance during the last two decades. Several studies have shown that treatment with antidepressants such as Fluoxetine is associated with enhanced plasticity in control animals, especially in regions such as the visual cortex, the hippocampus and the medial prefrontal cortex. More recently, the basolateral amygdala has been shown to be affected by Fluoxetine leading to a reopening of critical period-like plasticity in the fear and aggression circuits. One of the key elements triggering this type of brain plasticity are inhibitory networks, especially parvalbumin interneurons. However, recent work on fast-acting antidepressants has shown also an important role for somatostatin interneurons. Here we show that Fluoxetine reorganizes inhibitory circuits through increased expression of the plasticity-related molecule PSA-NCAM which regulates interneuronal structure and connectivity. In addition, we demonstrate that treatment with this antidepressant alters the structure of somatostatin interneurons both at the level of dendritic spines and of axonal en passant boutons . Our findings suggest that new strategies targeting somatostatin interneuron activity might help us to better understand depression and the action of antidepressants.